Incorporating immune cell surrogates into a full-thickness tissue equivalent of human skin to characterize dendritic cell activation - Johanna Maria Hölken; Anna-Lena Wurz; Katja Friedrich; Patricia Böttcher; Dounia Asskali; Holger Stark; Jörg Breitkreutz; Timo Buhl; Lars Vierkotten; Karsten Rüdiger Mewes; Nicole Teusch (Scientific Reports)
Abstract In the past decades studies investigating the dendritic cell (DC) activation have been conducted almost exclusively in animal models. However, due to species-specific differences in the DC subsets, there is an urgent need for alternative in vitro models allowing the investigation of Langerhans cell (LC) and dermal dendritic cell (DDC) activation in human tissue. We have engineered a full-thickness (FT) human skin tissue equivalent with incorporated LC surrogates derived from the human myeloid leukemia-derived cell line Mutz-3, and DDC surrogates generated from the human leukemia monocytic cell line THP-1. Topical treatment of the skin models encompassing Mutz-LCs only with nickel sulfate (NiSO4) or 1-chloro-2,4-dinitrobenzene (DNCB) for 24 h resulted in significant higher numbers of CD1a positive cells in the dermal compartment, suggesting a sensitizer-induced migration of LCs. Remarkably, exposure of the skin models encompassing both, LC and DDC surrogates, revealed an early sensitizer-induced response reflected by increased numbers of CD1a positive cells in the epidermis and dermis after 8 h of treatment. Our human skin tissue equivalent encompassing incorporated LC and DDC surrogates allows the investigation of DC activation, subsequent sensitizer identification and drug discovery according to the principles of 3R.